The Influence of Product Quality and Price on Purchasing Decisions at Tanjung Fashion Stores in West Jakarta - Jannah, Ramadhaniatun; Munarsih, Munarsih (Journal of Social Science and Business Studies, 2026)
This study aims to analyze the effect of product quality and price on purchasing decisions at Tanjung Fashion Store in West Jakarta. The increasing competition in the retail fashion industry requires business to understand consumer preferences, particularly regarding product quality and pricing strategies. This research uses a quantitative associative approach with a sample of 99 consumers selected using simple random sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that product quality and price have a positive and significant effect on purchasing decisions. Product quality contributes 79% to purchasing decisions, while price contributes 75,6%. Simultaneously, product quality and price have a significant influence with a contribution of 85,4%. These findings indicate that consumers tend to consider both quality and price when making purchasing decisions. This study contributes to the development of marketing management, especially in understanding consumer purchasing behavior. Practically, the results provide recommendations for business owners to improve product quality and adjust pricing strategies to enhance consumer purchasing decisions.